Constitutional Review of Covid-19 Law at Indonesia Constitutional Court - Qurrata Ayuni (UNES Law Review, 2023)
This paper analyzes the constitutionality of Law Number 2 of 2020 concerning COVID-19 which was originally passed as emergency legislation in the form of “government regulation in lieu of law”. The COVID-19 Law reaps pros and cons because it is considered to have the potential to give birth to abuse of power in times of crisis. Grounded by final decision of The Constitutional Court, this paper raises three main issues; First, the vital role of judicial power in providing checks and balances in an emergency situation. Second, the prohibition of granting immunity to the practice of irregularities in state finances in times of crisis. Third, the need for a time limit for granting discretion caused by COVID-19 to ensure legal certainty. Through the method used, namely normative juridical, conclusions were obtained regarding the urgency of the role of the power of the Constitutional Court in Indonesia as the protector of the Constitution in the COVID-19 emergency.